1995
DOI: 10.1111/j.1365-2133.1995.tb08668.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of in situ detection of histone mRNA in the assessment of epidermal proliferation: comparison with the Ki67 antigen and BrdU incorporation

Abstract: The labelling index is commonly used as a measure of proliferation. However, the use of tritiated thymidine or BrdU labelling of S-phase cells is limited to prospective samples. We have employed an oligonucleotide cocktail complementary to the mRNA species encoding the replication-dependent histones H2B, H3 and H4 for non-isotopic in situ hybridization (NISH), and have compared the resultant proliferation indices in normal skin with those obtained by bromodeoxyuridine (BrdU) incorporation and by Ki67 immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 20 publications
3
25
1
2
Order By: Relevance
“…2). In other proliferating cell populations, like epithelial cells or different tumor cells, a similar ratio between markers for the S phase alone (i.e., [ 3 H]thymidine incorporation), and proliferation-associated markers, including Ki67, has been described (17). Evaluation of Ki67 immunoreactivity revealed a doubling of the mitotic index during EAE, compared with both control and adjuvant-injected rats (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…2). In other proliferating cell populations, like epithelial cells or different tumor cells, a similar ratio between markers for the S phase alone (i.e., [ 3 H]thymidine incorporation), and proliferation-associated markers, including Ki67, has been described (17). Evaluation of Ki67 immunoreactivity revealed a doubling of the mitotic index during EAE, compared with both control and adjuvant-injected rats (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Recent immunohistochemical studies have been useful for the detection of proliferating cells in tissue samples using polyclonal or monoclonal antibodies against the proliferating cell nuclear antigens (1-4), P53 (5,6) and Ki67 (4)(5)(6)(7)(8). The immunohistochemistry of Ki67 was originally limited to frozen sections, however, as a result of recent developments of the MIB-1 and MIB-3 antibodies, it is now available in paraffin-embedded specimens (6,9,10). The antigen retrieval technique using autoclaving or microwave treatment prior to immunostaining also proves beneficial to retrospective studies.…”
mentioning
confidence: 99%
“…Histone mRNAs are tightly regulated during the cell cycle, allowing the synthesis of histone proteins to occur coordinately with the replication of DNA. In malignant tumors, upregulation of histone mRNA indicates proliferative activity of tumor cells, and many studies have demonstrated that histone mRNA accumulates in tumors (14)(15)(16). In most previous studies, histone levels have been measured by only considering H3 core histone levels.…”
Section: Discussionmentioning
confidence: 99%